Stylised features of consumer price setting behaviour in Portugal : 1992–2001 - Dias, Mónica Costa (2018)
This paper identifies the empirical stylized features of consumer price setting behavior in Portugal using two micro-datasets underlying the consumer price index. The main conclusions are: one in every four prices change each month; there is a considerable degree of heterogeneity in price setting practices; prices of goods change more often than prices of services; price reductions are common, as they account to around 40% of total price changes; price changes are, in general, sizeable; finally, the price setting patterns seem to depend on the level of inflation as well as on the type of outlet.